2012
DOI: 10.1155/2012/946063
|View full text |Cite
|
Sign up to set email alerts
|

Becoming Socialized into a New Professional Role: LPN to BN Student Nurses' Experiences with Legitimation

Abstract: This paper presents findings from a qualitative descriptive study that explored the professional socialization experiences of Licensed Practical Nurses (LPNs) who attended an online university to earn a Baccalaureate degree in nursing (BN), a prerequisite to writing the Canadian Registered Nurse (RN) qualifying exam. The project was framed from a constructivist worldview and Haas and Shaffir's theory of legitimation. Participants were 27 nurses in a Post-LPN to BN program who came from across Canada to complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…In the literature, this unintentional and unplanned learning has been discussed under the concept of a hidden curriculum. Similar to this research, other studies [3537] have reported that students in healthcare fields learn professional attitudes, values, norms and rituals through the hidden curriculum of their clinical education. The possibilities in achieving professional socialisation through the hidden curriculum indicates a need for nursing educators to reflect on our own nursing programmes.…”
Section: Discussionsupporting
confidence: 85%
“…In the literature, this unintentional and unplanned learning has been discussed under the concept of a hidden curriculum. Similar to this research, other studies [3537] have reported that students in healthcare fields learn professional attitudes, values, norms and rituals through the hidden curriculum of their clinical education. The possibilities in achieving professional socialisation through the hidden curriculum indicates a need for nursing educators to reflect on our own nursing programmes.…”
Section: Discussionsupporting
confidence: 85%
“…Studies of other second‐level nursing roles have reported similar issues with role identity (Janzen et al, 2013) and organisational failings with job descriptors have been identified in a review of nursing roles (Kusi‐Appiah et al, 2018). Other studies have reported that trust and value developed over time helps to cement identity for these nursing roles within healthcare teams (Huynh et al, 2011) (Melrose et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Socialization is a process of acquiring individual identity in which he learns required values, norms and skills for serving his social task as an effective person his unique position 5 .Socialization a basic concept in nursing that is due to interaction among interpersonal, intrapersonal and work functional relationships 6 . These relationships give members the opportunity to organize themselves and their resources and solve their problems by cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…These relationships give members the opportunity to organize themselves and their resources and solve their problems by cooperation. In fact, professional socialization is a learning process of the professional roles 5 . It consist of anticipatory, accommodation and role management .The process to achieve required professional norms ,values and skills for professional survival is not well known 7 .…”
Section: Introductionmentioning
confidence: 99%